THE IMPACT OF DISCIPLINE IN MEDIATING THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE (Case Study : PT. Tata Indah Sarana) - Irvan Sutia; Titing Widyastuti (Jurnal Scientia, 2023)
Business competition in the era of increasingly fierce globalization and along with increasingly rapid technological advances, requires companies to immediately adapt to environmental changes that occur in the business environment. Whether or not a company succeeds in competition depends on how the company can adapt in the face of change and produce a performance that matches customer expectations. There are many ways that companies can create competitive advantage, but basically the main key to competitive advantage lies in the quality of human resources. As a Private Company engaged in export import licensing, Spi, Iron, Steel, Forestry and others face tight competition against similar companies. The current condition of PT. Tata Indah Sarana (TIS) is felt to be not optimal, this can be seen from the performance achievements of the company PT. Tata Indah Sarana (TIS) still needs improvement. Based on the above phenomenon, the author tries to research the Impact of Discipline in Mediating the Influence of Transformational Leadership and Organizational Culture on Employee Performance (Case Study: PT. Tata Indah Sarana). The research was conducted at PT. Tata Indah Sarana (TIS), with a research population of 35 employees, due to population constraints, the sample taken was saturated as 32 respondents, because leaders and researchers were not used as responses to data collection using questionnaire method techniques, and direct observation. And for data analysis using the Smart Partial Least Square (PLS) analysis method version 3.0, for data tests used in this study are reliability tests, validity tests, statistical tests and classical assumption tests. The results of the H1 study: Transformational leadership has a partial effect on the performance of PT. Tata Indah Sarana (TIS), H2: Organizational culture has a partial effect on the performance of PT. Tata Indah Sarana (TIS), H3: Transformational leadership has a partial effect on the work discipline of PT. Tata Indah Sarana (TIS), H4: Organizational culture has a partial effect on the work discipline of PT. Tata Indah Sarana (TIS), H5: Discipline affects the performance of PT. Tata Indah Sarana (TIS), H6: Discipline mediates transformational leadership towards the performance of PT. Tata Indah Sarana (TIS), H7: Discipline mediates organizational culture on the performance of PT. Tata Indah Sarana (TIS).